Revisiting Battistini: Pleistocene Coastal Evolution of Southwestern Madagascar. (27th December 2022) - Boyden, Patrick; Weil-Accardo, Jennifer; Deschamps, Pierre; Godeau, Nicolas; Jaosedy, Nicolas; Guihou, Abel; Rajaonarivelo, Mamy Nirina; O'Leary, Michael; Humblet, Marc; Rovere, Alessio
The study of paleo shorelines, particularly of those formed during the late Quaternary, provides robust insights into past climate variability. Advances in surveying techniques and chronological methodologies have dramatically improved the inter-comparability of regional and basin-wide paleo shoreline surveys. However, these advances have been applied unevenly across the globe. This is especially true in southwestern Madagascar, where, in the 1960s and 1970s, emerged Pleistocene beach and reef facies were first described in detail and dated to Marine Isotope Stage (MIS) 5a using U–Th alpha activity counting by french geologist René Battistini. Now, 50 years on, no further analysis of the coastal sequence has been made. In this study, we present an updated late Pleistocene coastal evolution model for the southwestern Madagascar coast. Utilizing a combination of Structure-from-Motion/Multi-View Stereo techniques and differential Global Navigation Satellite System surveys, we have created five high-resolution 3D outcrop reconstructions that have, in turn, been chronologically constrained using 10 U-series ages from both in situ and reworked coral samples. Our data suggest that the emerged reef was deposited during MIS 5e (∼125 ka), then was covered by intertidal and beach sediment (including redeposited coral clasts of MIS 5e age), and finally capped off by thick eolianites. This sequence would suggest that the local sea level must have remained stable throughout MIS 5e in order to allow for the progradation of both the beach and reef environments.